2015
DOI: 10.1002/hed.23969
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression as predictor of local recurrence risk in oral squamous cell carcinoma

Abstract: MiRNAs are differentially expressed in OSCC versus normal samples. The expression of 4 prognostic miRNA signatures is able to predict recurrence risk independently from other clinical factors in OSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E189-E197, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…Interestingly, high expression of four of these miRNAs (miR-96-5p, miR-21-3p, miR-21-5p, and miR-429) was previously shown to be predictive of recurrence in head and neck squamous cell carcinoma. 15,16 Expression of these four miRNAs in peritumors was intermediate to that of tumoral and normal tissues, except for miR-429, which showed similar expression levels in tumoral and peritumoral tissues (Supplementary Figure S1). Validation of altered expression level of these miRNAs between peritumoral and normal tissues was performed by RT-qPCR on a series of 132 peritumors and 18 normal tissues (Figure 2e).…”
Section: Histologically Tumor-free Peritumor Tissue From Head and Necmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, high expression of four of these miRNAs (miR-96-5p, miR-21-3p, miR-21-5p, and miR-429) was previously shown to be predictive of recurrence in head and neck squamous cell carcinoma. 15,16 Expression of these four miRNAs in peritumors was intermediate to that of tumoral and normal tissues, except for miR-429, which showed similar expression levels in tumoral and peritumoral tissues (Supplementary Figure S1). Validation of altered expression level of these miRNAs between peritumoral and normal tissues was performed by RT-qPCR on a series of 132 peritumors and 18 normal tissues (Figure 2e).…”
Section: Histologically Tumor-free Peritumor Tissue From Head and Necmentioning
confidence: 99%
“…[12][13][14] In particular, our group together with others has observed a correlation between the expression of specific miRNAs and outcome of head and neck squamous cell carcinoma patients. 12,[14][15][16] Here, we aimed at identifying key alterations of miRNAs expression occurring in tumor-surrounding mucosa (referred to as 'peritumoral' mucosa hereafter) from head and neck squamous cell carcinoma patients, which predict local recurrence. In particular, the identification of a predictive miRNA signature in peritumoral tissues may have relevance for early detection of minimal residual disease and of pre-cancer molecular alterations implicated in malignant transformation.…”
mentioning
confidence: 99%
“…Several aberrantly expressed miRNAs have been recognized in OSCC, especially in chemoresistant OSCC, suggesting their critical roles in tumorigenesis and cancer recurrence. Moreover, miRNAs have been reported to function as prognostic indicators for relapse in patients with OSCC . Among these miRNAs, let‐7 family members have been found to be dysregulated in a variety of cancers and widely viewed as tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs have been reported to function as prognostic indicators for relapse in patients with OSCC. 9 Among these miRNAs, let-7 family members have been found to be dysregulated in a variety of cancers 10,11 and widely viewed as tumor suppressors. It has been shown that let-7…”
mentioning
confidence: 99%
“…Many factors, such as arecoline, are oxidative inducers (3). The five-year survival of OSCC remained low and this malignancy tended to relapse after treatment (4). Therefore, it is important to specify the molecular dysregulation in the regulatory axis contributive to OSCC pathogenesis to develop therapeutic modalities (5).…”
Section: Introductionmentioning
confidence: 99%